La medicina en los siglos XI y XII a partir de la Alexiada de Ana Comneno - Iommi Echeverría, Virginia (Byzantion Nea Hellás, 2015)
The Alexiad displays three fundamental aspects of Anna Comnena‘s medical knowledge. First of all she explains her father‘s disease through her knowledge of humoralism, rooted in a close and deep reading of classical authors. Besides, in the description of his therapy, Anna deals with an essential feature of humoral theory: its ambiguity. Finally, in her account, although science and religion are considered together, a clear distinction is made between medicine and faith.